2009
DOI: 10.1108/13522750910948761
|View full text |Cite
|
Sign up to set email alerts
|

Decision system analysis of advertising agency decisions

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Often, in the real world, the problem itself is not a "given," but, instead, searching for significant problems to which organizational attention should be turned becomes an important organizational task [HONE SENSEMAKING SKILLS]. (Cyert et al 1956, p. 237) Cyert et al (1956) is an insider's study in the B2B CSR literature-a well-spring reference for the reports that follow its publication (e.g., Mintzberg, Raisinghani, & Theoret, 1976;Vyas and Woodside 19984;Na, Marshall, & Woodside, 2009). Note that the fourth principle relates directly to Weick's (1979) …”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Often, in the real world, the problem itself is not a "given," but, instead, searching for significant problems to which organizational attention should be turned becomes an important organizational task [HONE SENSEMAKING SKILLS]. (Cyert et al 1956, p. 237) Cyert et al (1956) is an insider's study in the B2B CSR literature-a well-spring reference for the reports that follow its publication (e.g., Mintzberg, Raisinghani, & Theoret, 1976;Vyas and Woodside 19984;Na, Marshall, & Woodside, 2009). Note that the fourth principle relates directly to Weick's (1979) …”
Section: )mentioning
confidence: 99%
“…Hulbert, Farley, and Howard (1972) were the first to describe the theory and empirical steps of doing DSA in B2B contexts. Examples with elaborations of the method in B2B contexts include the following studies: Capon and Hulbert (1975), Howard, Hulbert, and Farley (1975), Hulbert (1981, Johnston and Bonoma (1981), Na, Marshall, and Woodside (2009), and Vyas and Woodside (1984). Woodside's (2003) study.…”
Section: Decision Systems Analysis (Dsa)mentioning
confidence: 99%
“…The model can also offers several insights into stakeholder relationships. Most previous studies suggested that client engagement in the process was limited to their involvement in strategy creation and final work approval (Na, Marshall, and Woodside 2009). The shift that can be observed and is described in the research, presents the evolving relationship between agency and client, showing that some agencies allow the client to validate ideas during the earlier stages of the process (Turnbull and Wheeler 2017).…”
Section: Sequential and Stage Models Of The Advertising Creative Processmentioning
confidence: 77%
“…The analysis can get extremely complex if too many individuals' thought processes are included. As in a related method, Decision System Analysis, that seeks to map managerial action processes, multiple decision patterns can be collapsed and combined to either allow comparison between specific situations or groups, or to simplify the overall pattern to make sense of the major parameters of a group decision (Na, Marshall, & Woodside, 2009). This simplification process carries with it the all the concomitant risks of concealing individual differences and of yielding to observer bias; but the risks can be minimized through proper triangulation of any categorization process.…”
Section: Constructing a Cognitive Mapmentioning
confidence: 99%